THE EFFECT OF THE OUTCOMES OF VILLAGE DECISIONS ON COMMUNITY DIGNITY DURING THE PANDEMIC IN BONGO VILLAGE III - Ni Nengah Sinarwati; William I. Mooduto; Sukrianto (Journal of Economic, Business, and Administration (JEBA), 2023)
The goal of this study was to ascertain community satisfaction with village decision-making outcomes during a pandemic in Bongo III Village. According to Sugiyono (2018:35-36), the research method is quantitative, which is depicted as research based on the positivist philosophy, which is used to study specific populations or samples, collect data using research instruments, and analyze data quantitatively/statistically with the goal of testing hypotheses that have been designated set. This study was conducted in order to provide evidence and confirmation. According to the research findings and discussion on the effect of village deliberation decisions on community satisfaction in Bongo III Village, it is concluded that village deliberation decisions did not affect community satisfaction in Bongo III Village. This is because some types of discussion continue to fail. Both planned and ad hoc village deliberation. This is demonstrated by the absence of a concurrent influence of the independent variable (X) on the dependent variable in hypothesis testing (Y). This demonstrates that when t count > t table or 1.389 > 1.660, the statistical result of the village deliberation decision variable with ( = 5%) has a negative and minor effect on community satisfaction. A significant value (0.168 > 0.05) demonstrates this.